Reform of the Canada Pension Plan : Analytical Considerations - Kramer, Charles; Li, Yutong (Washington, D.C. : International Monetary Fund, 1997)
Like other transfer programs, a pay-as-you-go public pension system can significantly affect economic behavior and, hence, relative prices and macroeconomic aggregates. This paper illustrates some of these effects, which are important in weighing options for reforming public pensions, in the context of a stylized model of the Canadian economy. It shows that introducing such a system can reduce aggregate saving, income, and wages and increase interest rates. It also shows that a significant part of the distortion can occur because benefits are not explicitly linked to contributions and that creating a linkage can reduce the distortions associated with the wage tax that funds plan contributions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet